Distribution of glycine receptors on the surface of the mature calyx of Held nerve terminal - Trojanova, Johana; Kulik, Akos; Janacek, Jiri; Kralikova, Michaela; Syka, Josef; Turecek, Rostislav (Frontiers in Neural Circuits, 2014)
The physiological functions of glycine receptors (GlyRs) depend on their subcellular locations. In axonal terminals of the central neurons, GlyRs trigger a slow facilitation of presynaptic transmitter release; however, their spatial relationship to the release sites is not known. In this study, we examined the distribution of GlyRs in the rat glutamatergic calyx of Held nerve terminal using high-resolution pre-embedding immunoelectron microscopy. We performed a quantitative analysis of GlyR-associated immunogold (IG) labeling in 3D reconstructed calyceal segments. A variable density of IG particles and their putative accumulations, inferred from the frequency distribution of inter-IG distances, indicated a non-uniform distribution of the receptors in the calyx. Subsequently, increased densities of IG particles were found in calyceal swellings, structures characterized by extensive exocytosis of glutamate. In swellings as well as in larger calyceal stalks, IG particles did not tend to accumulate near the glutamate releasing zones. On the other hand, GlyRs in swellings (but not in stalks) preferentially occupied membrane regions, unconnected to postsynaptic cells and presumably accessible by ambient glycine. Furthermore, the sites with increased GlyR concentrations were found in swellings tightly juxtaposed with GABA/glycinergic nerve endings. Thus, the results support the concept of an indirect mechanism underlying the modulatory effects of calyceal GlyRs, activated by glycine spillover. We also suggest the existence of an activity-dependent mechanism regulating the surface distribution of α homomeric GlyRs in axonal terminals of central neurons.